Análise da marcha de indivíduos hemiparéticos submetidos a instabilidade - Oliveira, Ludmila Costa Toni de (2008)
Introduction: The hemiparesis occurring after a stroke generates walking disorders and functional deficits. The purpose of this study was to verify the influence of an uneven surface (medium-density foam) on the gait cycle of hemiparetic patients. Method: This exploratory, transversal study included 33 subjects: 18 stroke patients (6 months post-stroke onset or more) and 15 healthy individuals (control group) matched by age and gender. Subjects were able to ambulate without walking-aid for a 5-m minimum distance. A 2D kinematics gait analysis was performed comparing gait cycles in the two surfaces (regular and foam). Five different angles were quantified: shoulder segment and pelvic segment (frontal plane), and hip, knee and ankle angles (sagittal plane). Gait velocity and stride length were also calculated. Data was compared using variance and co-variance analyses having gait velocity as co-variable (post-hoc tests were performed when necessary). An alpha level of 0.05 was chosen for significance. Results: There were significant differences between groups and surfaces in all measured parameters but the pelvic angle, which was similar in all cases. Patients presented smaller angle excursions as compared in to healthy subjects, excepting the shoulder segment, which showed greater excursion. Both groups increased their excursions on the uneven surface. The velocity adjustment removed the difference between groups for hip and shoulder angles. Conclusion: Even though hemiparetic patients revealed smaller joint excursions in the sagittal plane they showed a similar change on the gait standard as compared to healthy individuals, which was demonstrated with an increase in joint excursion but lower movement range when comparing the 2 surfaces.